2002
DOI: 10.1111/j.1752-7325.2002.tb03436.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Patient, Visit, and Oral Health Factors on Dental Service Provision

Abstract: After controlling for oral health, visit characteristics persisted as significant predictors of services, with nonemergency visits, insurance, and capital city location associated with more favorable service mix patterns. Higher socioeconomic status areas and payment scale ratings also were associated with a better service pattern in particular service areas. These findings show that a wide range of factors, in addition to oral health, contribute to variation in service provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 47 publications
(19 reference statements)
4
30
1
Order By: Relevance
“…Some authors have asserted that there is little correlation between dentists' stated attitude as reported in questionnaire surveys and their therapy decisions in clinical practice. [11][12][13] Dentists putting their treatment philosophies into practice are forced to modify them as they need to consider the combined realities of patient characteristics and practice circumstances. Practicebased surveys thus add complementary data providing insight into real-world practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have asserted that there is little correlation between dentists' stated attitude as reported in questionnaire surveys and their therapy decisions in clinical practice. [11][12][13] Dentists putting their treatment philosophies into practice are forced to modify them as they need to consider the combined realities of patient characteristics and practice circumstances. Practicebased surveys thus add complementary data providing insight into real-world practices.…”
Section: Discussionmentioning
confidence: 99%
“…This has implications in terms of appropriateness of care and equity in the delivery of dental care. [11][12][13][37][38][39] Many epidemiological studies have explored the relationship between patient factors and the characteristics of restorative treatments, 8 but few have explored the impact of the ''dentist'' profile. Multivariate models used to describe dental service rates have reported wide variations among providers that were not explainable by differences in patient needs or demand for care.…”
Section: Discussionmentioning
confidence: 99%
“…The findings by reason for visit support previous studies that have shown less favourable service patterns in terms of lower rates of preventive services and higher rates of extraction for emergency visits motivated by relief of pain. 19 Previous studies have also identified more favourable service patterns by location in terms of higher rates of preventive services at capital city locations, 20 with topical fluoride provided at higher rates at capital city locations. 21 While the lower rate of endodontic services at capital city locations observed in this study may seem counter-intuitive given that such higher level interventions may be expected to be provided at higher rates in capital cities, it should be noted that the present study is restricted to patients with a diagnosis of caries.…”
Section: Visit Type Location and Socio-economic Statusmentioning
confidence: 91%
“…However, for adults the receipt of public care in Australia has been associated with more extractions and less preventive and maintenance care . Dental service provision in private general practice has been associated with a range of dental provider characteristics [Brennan and Spencer, 2005] as well as patient and practice characteristics [Brennan and Spencer, 2002]. Further, rates of relief of pain and extractions have been associated with lower income and lower education [Roberts- .…”
Section: Discussionmentioning
confidence: 99%